Maternal Cannabis Use Alters Ventral Striatal Dopamine D2 Gene Regulation in the Offspring - DiNieri, Jennifer A.; Wang, Xinyu; Szutorisz, Henrietta; Spano, Sabrina M.; Kaur, Jasbir; Casaccia, Patrizia; Dow-Edwards, Diana; Hurd, Yasmin L. (BIOLOGICAL PSYCHIATRY, 2011)
Prenatal cannabis exposure has been linked to addiction vulnerability, but the neurobiology underlying this risk is unknown. Striatal dopamine and opioid-related genes were studied in human fetal subjects exposed to cannabis (as well as cigarettes and alcohol). Cannabis-related gene disturbances observed in the human fetus were subsequently characterized with an animal model of prenatal Δ-9-tetrahydrocannabinol (THC) (.15 mg/kg) exposure. Prenatal cannabis exposure decreased dopamine receptor D2 (DRD2) messenger RNA expression in the human ventral striatum (nucleus accumbens [NAc]), a key brain reward region. No significant alterations were observed for the other genes in cannabis-exposed subjects. Maternal cigarette use was associated with reduced NAc prodynorphin messenger RNA expression, and alcohol exposure induced broad alterations primarily in the dorsal striatum of most genes. To explore the mechanisms underlying the cannabis-associated disturbances, we exposed pregnant rats to THC and examined the epigenetic regulation of the NAc Drd2 gene in their offspring at postnatal day 2, comparable to the human fetal period studied, and in adulthood. Chromatin immunoprecipitation of the adult NAc revealed increased 2meH3K9 repressive mark and decreased 3meH3K4 and RNA polymerase II at the Drd2 gene locus in the THC-exposed offspring. Decreased Drd2 expression was accompanied by reduced dopamine D2 receptor (D2R) binding sites and increased sensitivity to opiate reward in adulthood. These data suggest that maternal cannabis use alters developmental regulation of mesolimbic D2R in offspring through epigenetic mechanisms that regulate histone lysine methylation, and the ensuing reduction of D2R might contribute to addiction vulnerability later in life.